The non-silent world : acoustic responses of white-beaked dolphins (lagenorhynchus albirostris) to changes in maritime traffic : a case study during the covid-19 anthropause in Skjálfandi Bay, Iceland - Mathieu Reverberi 1998- (2023)
The effects of anthropogenic noise on marine fauna remain understudied. Nevertheless, the worldwide spread of Covid-19 and the ensuing period of reduced human activity – named anthropause by scientists - created an opportunity for researchers to study the effects of decreased human-made noise on wildlife. Skjálfandi Bay in the northeast of Iceland is home to a large population of cetaceans. In this wide bay, whale-watching operations began in 1995 and continue to attract hundreds of thousands of tourists every year. In this thesis, changes in maritime traffic associated with the Covid-19 pandemic have been quantified. The impact of vessels on the social behavior of white-beaked dolphins (Lagenorhynchus albirostris) were then investigated using acoustic recordings, visual observations, and Automatic Identification System (AIS) vessel traffic data. A hydrophone was deployed over the summers of 2020 and 2022 in Skjálfandi Bay. Acoustic data from 2020 were repurposed in order to listen to what happened in our oceans when they went quiet and compare with 2022. This study found that white-beaked dolphins tend to whistle more, and therefore communicate more when human activity was reduced in Skjálfandi Bay; whether it is during periods of low traffic (evening and night) or when local maritime traffic was disrupted in 2020. A better understanding of the anthropogenic impacts on marine fauna at a local scale can lead to better enforced and more effective regulations in Skjálfandi Bay, and also could serve as a basis for further studies elsewhere in Iceland or in other countries. This research could also be used by local stakeholders to support the implementation of a marine protected area in Skjálfandi Bay. Áhrifin af manngerðum hávaða á sjávardýraríki eru áfram of lítið rannsökuð. Engu að síður, skapaði heimsútbreiðsla Covid-19 og eftirfylgjandi tímabil með minni virkni manna – nefnt mannkyns-kreppa af vísindamönnum - tækifæri fyrir rannsakendur að rannsaka áhrifin af minnkuðum manngerðum hávaða á villtar lífverur. ...